Early vs. Delayed Laparoscopic Cholecystectomy in Acute Calculous Cholecystitis: A Comparative Analysis of Outcomes and Complications - Vipul Lad; Jenish Modi; Parag Godhani (National Journal of Medical Research)
Background: This study compares early laparoscopic cholecystectomy (ELC) and delayed laparoscopic cholecystectomy (DLC) in patients with acute calculous cholecystitis to determine the optimal timing for surgery. The study aims to assess the outcomes, complications, and safety of both approaches.